Application of Treg/Tef in liver cancer T + A curative effect prediction and prognosis evaluation - LI SIQI; YE LINSEN; YANG YANG; LI KUN; YU HAOYUAN (2023)
The invention relates to application of Treg/Tef in liver cancer T + A curative effect prediction and prognosis evaluation. In-depth study is carried out on liver cancer tissues after T + A treatment, and it is found that the ratio of Treg/Te f is obviously related to liver cancer recurrence and prognosis; by detecting PBMCs in blood of a liver cancer subject after T + A treatment and the ratio of Treg/Tef in liver cancer tissues, the curative effect and prognosis of the liver cancer patient after T + A treatment can be reasonably predicted, that is, the expression level of Treg/Tef can be used as a biomarker for predicting the curative effect and prognosis of T + A treatment of liver cancer. By detecting the Treg/Tef expression level in blood and tumor tissues of a subject, preparation work can be made in advance for whether the subject continues to accept T + A treatment or a treatment mode to prevent liver cancer development, unexpected health damage caused by rapid development and deterioration of disease